Kota yang Teratur sebagai Kesan Kota yang Baru - Kurniawati, Wakhidah (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
The average perception of the people on a city (the city image) has an important role in building pride and comfort in the community’s life, and acts as a selling point to attract visitors and investment. A city’s image can be good, bad, or a mix of both, depending on the visual of the eyes on the street. In her book The Death and Life of Great American Cities, Jane Jacobs (1969) said “if a city’s streets look interesting, the city looks interesting, if they look dull, the city looks dull. This justifies the importance of the quality of the outdoor environment (in this case the streets) as a part of the image of a city. Singapore is one the cities in world’s perceived to have the best city image. Singapore is well known to be tidy and discipline through its enforcement of heavy fines enforced to offenders giving it its renowned nickname as ‘the fine city’. The fines act as both punishment to offenders and controller of the city’s order through the application of watch cameras throughout the city. Education of rules was well in place thus the people can still life comfortably without feeling being pressured. It is a different matter with Indonesia, many of our cities still have untidy city image as a result of weak enforcement of city rules as if they are non-obligatory. To recover the good image, cities need to embrace the city rules as a new fundamental for thinking about the beauty of a city.